Konsep Serta Makna Sunat Menurut Perjanjian Lama dan Kaitannya dengan Kesehatan Secara Medis - Gephta, Hendra; Panjaitan, Firman (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Circumcision is a crucial issue to be discussed and discussed, especially when trying to explain the meaning of the People of God in the Old Testament. Circumcision is a sign of the Covenant (berith) that God required for the Israelites, which began when God established the Covenant with Abraham. However, circumcision does not only have this definition but has a broader meaning. By using qualitative research methods, especially with a literary approach, this article shows that in its development circumcision does not just talk about the characteristics and requirements of being God's people, but also becomes a measure of cleanliness that needs to be maintained by God's people. Cleanliness is meant here not only physical cleanliness, but also spiritual cleanliness. Thus, circumcision is necessary to maintain cleanliness and physical health as well as spiritual cleanliness, as ordered by the Old Testament.